Electronic Books Based with a Contextual Approach on Reading Material in Indonesian Language Content for Fourth Grade Elementary School - Ningsih, Ni Putu Mia Hughestia; Agung, Anak Agung Gede (Universitas Pendidikan Ganesha, 2024)
Conventional learning is still carried out in Indonesian language learning. This causes students to get bored and not enthusiastic about learning. Based on this, this research aims to analyze the effectiveness of electronic books on student learning outcomes in class IV Indonesian language subjects. This research is development research that refers to the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. Research data collection methods and instruments were collected using questionnaires and multiple-choice tests. The research data was then analyzed descriptively qualitatively, quantitatively, descriptive statistics and inferential statistics. This research used 29 fourth grade students as subjects. The results of this research show that the media feasibility test by experts and respondents received very good qualifications and was suitable for use. The effectiveness test results show that H0 is rejected and H1 is accepted. So it can be concluded that the results of using Electronic Books based on the Contextual Approach are effectively used in the reading activities of class IV students. The implication of this research is that it is an example of the application of digital teaching materials for Indonesian language learning in elementary schools. Teachers are expected to always develop their competence in carrying out varied learning.